Gastrointestinal persistence of the probiotic bacteria Lactobacillus plantarum 423 and Enterococcus mundtii ST4SA, and their anti-listerial activity - Van Zyl, Winschau Fayghan (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.